Bear and bird : the stars and other stories [book with audioplayer] - Jarvis, 1985- (Jarvis, 1985- Bear and Bird, 2023)
"Bear and Bird are the best of friends, but yesterday they had a falling out. And although they can't quite remember why, each is sure that a new best friend is now in order. If Bear sends an anonymous letter floating down the river, will it be found by someone nice--someone with whom he has as much in common as he did with Bird? In this quartet of tales, the endearing duo is back to show that even friends who sometimes get their wires crossed can always be each other's best supporter--whether making plans to meet that go comically awry, baking hideously inedible surprise cakes, or savoring a starlit moment together (and getting carried away with wishes for just one more thing to make it perfect). With his signature subtle wit, irresistible art, and an underlying affection, Jarvis draws newly independent readers into a sweet friendship for the ages."--